Building Bridges among Women from Different Faith Traditions - Sevy, Rosa (2013)
This article describes the findings of a postdoctoral research project aimed to investigate best practices for inter-religious bridging. This investigation sought to understand the experiences of mainly Muslim, Jewish and Christian women, all mothers of elementary-aged school children, who engaged in an inter-religious encounter framed in the context of an 8-session parenting program. Utilizing an interdisciplinary theoretical framework and qualitative data collected through the researcher’s observations, interviews and a questionnaire based evaluation forms, this work suggests that engaging women from different faith traditions in inter-religious encounters not based on faith discussions has the potential to shift mutual anxieties, perceptions and stereotypes to more positive positions based on the commonalities discovered as women and mothers going through the challenges of parenthood. Engaging women from different faith traditions in initiatives aimed at exploring their common concerns and providing them with a safe space to engage in that discussion can prove very effective in facilitating dialogue and building bridges and perception change among participants.
Keywords: Inter-faith Dialogue; Inter-group Contact; Inter-religious Encounters; Jewish-Muslim-Christian; Parenting; Women